2022
DOI: 10.1002/anie.202116324
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Control of Molecular Cascade Reactions by a Reconfigurable DNA Origami Domino Array

Abstract: Inspired by efficient biomolecular reactions in the cell, versatile DNA nanostructures have been explored for manipulating the spatial position and regulating reactions at the molecular level. Spatially controlled arrangement of molecules on the artificial scaffolds generally leads to enhanced reaction activities. Especially, the rich toolset of dynamic DNA nanostructures provides a potential route towards more sophisticated and vigorous regulation of molecular reactions. Herein, a reconfigurable DNA origami d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…(D) Dynamic control of molecular cascade reactions on a reconfigurable DNA origami domino array (DODA). Reproduced with permission from ref . Copyright 2021 Wiley.…”
Section: Nanomaterials Templated By Dna Origamimentioning
confidence: 99%
See 1 more Smart Citation
“…(D) Dynamic control of molecular cascade reactions on a reconfigurable DNA origami domino array (DODA). Reproduced with permission from ref . Copyright 2021 Wiley.…”
Section: Nanomaterials Templated By Dna Origamimentioning
confidence: 99%
“…In addition, the structural continuity of the origami between the enzyme linkages affected the catalytic activity. Furthermore, Fan et al designed a reconfigurable DNA origami domino array (DODA) for the dynamic control of molecular cascade reactions . The DODA structure was used to anchor the reactants with nanometer spatial precision (Figure D).…”
Section: Nanomaterials Templated By Dna Origamimentioning
confidence: 99%
“…Nucleic acids are outstanding bricks for constructing ordered nanostructures, [89,90] and these nanostructures, often called DNA origami, can serve as scaffolds for enzyme assembly [91–95] . For example, Hao, Gang, Chen, Niemeyer, and other researchers have designed artful DNA structures to precisely control the position of immobilized enzymes [96–110] . However, most of the DNA‐enzyme complexation systems were manifested in vitro or for cell‐free synthesis, and those that regulate biosynthesis inside cells are relatively rare.…”
Section: Scaffolded Enzyme Assemblymentioning
confidence: 99%
“…[91][92][93][94][95] For example, Hao, Gang, Chen, Niemeyer, and other researchers have designed artful DNA structures to precisely control the position of immobilized enzymes. [96][97][98][99][100][101][102][103][104][105][106][107][108][109][110] However, most of the DNA-enzyme complexation systems were manifested in vitro or for cell-free synthesis, and those that regulate biosynthesis inside cells are relatively rare. Conrado et al reported an outstanding example of DNA-guided assembly of biosynthetic pathways in living cells.…”
Section: Nucleic Acids As Scaffoldsmentioning
confidence: 99%
“…Tile-based self-assembly methods [ 22 , 23 ] assemble basic motifs into structures through a periodic interaction between the motifs ( Figure 1 a). DNA origami-based self-assembly methods [ 24 , 25 ] utilize many short staple strands to bind a long, single DNA strand and fold it into a certain shape ( Figure 1 b). DNA brick-based self-assembly methods [ 26 , 27 ] combine hundreds of single strands into a designed structure, and the design process is similar to filling a canvas with pixels ( Figure 1 c).…”
Section: Introductionmentioning
confidence: 99%